Association between ABO blood types and pain perception. (2nd October 2017) - Simoni, Amalie Højmose; Jerwiarz, Anne; Randers, Amalie; Gazerani, Parisa
Abstract: Aim of the study: Pain perception is associated with different phenotypic characteristics such as sex, eye, and hair color. Hence, it is assumed that ABO blood type can also affect pain perception. Materials and methods: In order to investigate this hypothesis, an experimental study with healthy volunteers (18–40 years) was designed. The experimental procedure included a blood type test and two rounds of pressure pain threshold assessments separated by a cold pressor test. Pressure pain threshold was assessed bilaterally at the temporalis, masseter, and deltoid muscles, where the muscle sites were randomized. Cold pressor test was conducted by immersion of participants' non-dominant hand into iced water of 1–4 °C for 2 min. Results: Thirty-seven healthy volunteers, distributed in the four blood type groups, completed the study. Participants with blood type B scored the highest pressure pain thresholds at the examined craniofacial muscles, while participants with blood type AB tended to score the lowest. Furthermore, participants with blood type AB displayed the highest elevation in pressure pain thresholds after cold pressor test. Conclusions: Participants with blood type B displayed the lowest mechanical pain sensitivity and the blood type AB group exhibited the strongest conditioned pain modulation effect. These findings emphasize the necessity of considering ABO blood types in future pain research.